EFFECT OF AGE AND SEX ON MORPHOMETRIC MEASUREMENTS OF SAHELIAN GOATS IN FASKARI LOCAL GOVERNMENT AREA OF KATSINA STATE - Aliyu, A. M.; Rotimi, E. A.; Galadima, N. M. (FUDMA JOURNAL OF SCIENCES, 2021)
This research was conducted to determine the effect of age and sex on morphometric measurements and estimate correlation between body weights and morphological traits of Sahelian goat in Faskari Local Government Area, Katsina state. Experimental animals aged from 1-5 years were used for this study and were identified using physical appraisal. Physically healthy of both sexes and non-pregnant goats were sampled.  The pairs of permanent incisors in the dentition of the goat were used to determine age, body weight by using bathroom weighing scale (kg), linear measurements using flexible tailorâ€™s measuring tape and sex using physical observations. The results obtained, showed that age had significant (P<0.05) effects on RH, EL, HoL and TL, non-significant (PËƒ 0.05) effect was found on BW, NL and BL. Sex had significant effect on BW, BL, HG and HoL and non- significant effect (PËƒ 0.05) was found on RH, EL, TL and NL. Correlation coefficient between body weight and linear measurement shows that BW was highly correlated (P<0.01) with BL, HG and NL. BW was slightly correlated with RH and it was negatively correlated EL and HoL.